James Buchanan's theory of federalism: From fiscal equity to the ideal political order - Lars P. Feld (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2014)
The distinct characteristic in James Buchanan's thinking about federalism in contrast to the traditional theory of fiscal federalism is his view about fiscal competition. In this paper, it is demonstrated that this thinking went through three stages. From the 1950s to the beginning of the 1970s, his analyses were well embedded in the traditional fiscal federalism literature and concerned with equity and efficiency issues. In the Leviathan approach starting from the midseventies, he considered competition between jurisdictions as a means to restrict Leviathan governments. In his interpretation of federalism as an ideal political order, Buchanan binds these perspectives together and adds a procedural view: Federalism enables citizens to exert political control, it raises their interest in politics because one vote has more influence, and it facilitates to act morally within their moral capacity.
Keywords: H77; B31; D78; 330; James Buchanan; Fiscal Equity; Fiscal Competition; Federalism as Political Order